2022
DOI: 10.3389/fneur.2022.1032103
|View full text |Cite
|
Sign up to set email alerts
|

The not so hidden impact of interictal burden in migraine: A narrative review

Abstract: Migraine is a highly prevalent neurological disease of varying attack frequency. Headache attacks that are accompanied by a combination of impact on daily activities, photophobia and/or nausea are most commonly migraine. The headache phase of a migraine attack has attracted more research, assessment tools and treatment goals than any other feature, characteristic, or phase of migraine. However, the migraine attack may encompass up to 4 phases: the prodrome, aura, headache phase and postdrome. There is growing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 95 publications
0
12
0
Order By: Relevance
“…This headache disorder is characterized by recurrent headache attacks of moderate to severe intensity, which interfere with daily activity. The interictal symptoms of migraine include allodynia, hypersensitivity, photophobia, phonophobia, osmophobia, visual/vestibular disturbances, and motion sickness [ 2 ]. The Eurolight project revealed that interictal symptoms, reported in 26.0% of patients with episodic migraine (EM), caused loss of productivity [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…This headache disorder is characterized by recurrent headache attacks of moderate to severe intensity, which interfere with daily activity. The interictal symptoms of migraine include allodynia, hypersensitivity, photophobia, phonophobia, osmophobia, visual/vestibular disturbances, and motion sickness [ 2 ]. The Eurolight project revealed that interictal symptoms, reported in 26.0% of patients with episodic migraine (EM), caused loss of productivity [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Functional imaging studies corroborate changes in the brain during this interictal phase 39 . In addition to the aforementioned symptoms, the interictal burden of migraine is associated with photophobia, anxiety (fear of the next attack), depression (inability to make plans because of the possibility of having a migraine episode), motion sickness, fear of upcoming events, stigma (reluctance to tell others about their headaches), and worse interpersonal interactions with others 37,40 . Individuals experiencing interictal impact from migraine report having to alter their lifestyle to avoid triggers or in response to an impending attack 41 .…”
Section: Conducting the Interviewmentioning
confidence: 81%
“…Multiple studies have found that the migraine postdrome has negative effects on patients’ daily functioning and overall quality of life [ 3 , 9 , 15 , 22 ]. Our study revealed a weak positive correlation between the number of postdromal symptoms reported prompted and both HIT-6 and WHODAS scores.…”
Section: Discussionmentioning
confidence: 99%